UJI AKTIVITAS ANTIHIPERLIPIDEMIA EKSTRAK ETANOL DAUN ARA SUNGSANG (Asystasia gangetica) TERHADAP KADAR KOLESTEROL PADA MENCIT PUTIH JANTAN (Mus musculus) - Muflihah Fujiko; Shinta Naswa; Nova Arianti; Muharni Saputri; Dasopang, Eva Sartika (Indonesian Journal of Pharmaceutical and Clinical Research, 2024)
Hyperlipidemia can be treated with medication. However, the large side effects cause people to return to herbal medicine. Sungsang fig leaves contain flavonoid, tannin and saponin compounds that can reduce cholesterol levels. The stages of the procedure carried out are making simplisia, followed by cold extraction, namely maceration with ethanol p.a solvent as the solvent of choice. Furthermore, phytochemical screening of sungsang fig leaf extract and simplisia characterization studies were carried out. After that, anti-hyperlipidemia activity was tested in vivo using male white mice to determine the effect of reducing blood cholesterol levels with ethanol extract of sungsang fig leaves. The result of the decrease in cholesterol levels in white male mice from ethanol extract of sungsang fig leaves at a dose of 500 mg/kg BW was 41%. These results are 1.20 times greater than the dose of 125 mg/kg BW and 1.17 times greater than the dose of 250 mg/kg BW. Synergistic compounds to reduce cholesterol levels are flavonoids, tannins and saponins. The decrease in cholesterol levels from ethanol extract of sungsang fig leaves at a dose of 500 mg/kg BW is not significantly different from simvastatin 10 mg.